2019
DOI: 10.21082/jhort.v28n2.2018.p259-268
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Pilihan Model Kelembagaan untuk Pengembangan Perbenihan Bawang Merah Melalui True Shallot Seed di Jawa Timur (Choice Determination of Institutional model for Seed Development of Shallot through True Shallot Seed System in East Java)

Abstract: <p>Penggunaan biji true shallot seed (TSS) telah diperkenalkan sebagai salah satu alternatif penyediaan benih bawang merah yang sehat dan berkualitas tinggi yang tersedia dalam jumlah yang cukup bagi petani sepanjang tahun. Penggunaan TSS diharapkan dapat mengatasi persoalan kuantitas dan kualitas bawang merah konsumsi serta perbenihan bawang merah di Indonesia. Pembentukan kelembagaan yang tepat perlu dibangun sejalan dengan pengembangan TSS. Pembentukan kelembagaan yang baik dan kuat dapat menghasilkan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The Data were analysed by using Analytical Hierarchy Process (AHP) as the method can be utilized to choose one option among several available options [14]. The models offered to respondents were based on the previous study, as shown in Figures 1, 2, 3, and 4 [15]. Meanwhile, the criteria were used to choose the institution model options covered 1) Quality 2) Acceleration 3) Profitable 4) Risk and 5) Continuity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Data were analysed by using Analytical Hierarchy Process (AHP) as the method can be utilized to choose one option among several available options [14]. The models offered to respondents were based on the previous study, as shown in Figures 1, 2, 3, and 4 [15]. Meanwhile, the criteria were used to choose the institution model options covered 1) Quality 2) Acceleration 3) Profitable 4) Risk and 5) Continuity.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to that, the scope covered 1) province and 2) District/municipal area development. The AHP of TSS institution model in East Java is described as shown in Figure 5 [15].…”
Section: Methodsmentioning
confidence: 99%